Altered neural activation pattern during teeth clenching in temporomandibular disorders. (28th March 2016) - He, SS; Li, F; Gu, T; Liu, Y; Zou, SJ; Huang, XQ; Lui, S; Gong, QY; Chen, S
Abstract : Objective: The aim was to explore the neural activations during teeth clenching in TMDs patients pre‐ and post‐treatment. Subjects and Methods: Thirty TMDs patients and 20 controls underwent clinical evaluations and functional magnetic resonance imaging with a teeth clenching task. Eleven patients received repeat evaluation and imaging after wearing a stabilization splint for 3 months. Results: During teeth clench, the TMDs patients showed decreased positive activity in the left precentral gyrus, right and left inferior temporal gyrus, and left cerebellum and increased negative activations in the right medial prefrontal cortex ( P  < 0.05 after AlphaSim correction). The 11 TMDs patients after treatment showed a return to normal neural activity in these areas. No brain areas in TMDs patients showed differences in activation after treatment compared with the controls, except for an increase in activation in the right cerebellum in the 11 TMDs patients ( P  < 0.05 after AlphaSim correction). Conclusion: Decreased activations in cerebral areas associated with motor and cognitive functions in TMDs patients during teeth clenching were observed. Normalized activations of these areas happened in patients after routine treatment. These findings may facilitate the understanding of TMDs pathogenesis and the therapeutic mechanisms of the stabilization splint.